Low wages and problems for the employees in businesses - Nguyễn Thanh Tùng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The reality and many studies have shown that wages also have direct influence on workers’ personal life. The fact of having low wages forces workers to spend sparingly by reducing their living costs and failing to improve their essential needs such as food, clothing, transportation, childcare, education, etc. .. At the same time, they have to work overtime in order to increase their income. In addition to working time, workers also have to spend their time taking care of children and family. As a result, they do not have enough time to rest and participate in any social or recreational activities. Both mental and physical health of workers are not good because they always feel stressed and tired. On the basis of analyzing the impacts of low wages on workers’ lives, the author proposes some recommendations through identifying a living wage for them.